OPTIMIZING LETTUCE PRODUCTION THROUGH THE USE OF COMPOST PLANTING MEDIA TO INCREASE THE INCOME OF INDIGENOUS PAPUANS IN SORONG REGENCY - Sudirman, Hendra; Andriyan, Yoga; Athirah, Aldila Mawanti; Smur, Luksen Helkia; Rahakratat, Ramles; Saa, Apner; Puarada, Giffard R. K.; Fadan, Falentinus (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
This community service activity aims to increase the productivity of lettuce agriculture and the economic welfare of the indigenous Papuan people in Sorong Regency. Sorong Regency is still very dependent on other regions to meet the needs of vegetables because vegetable productivity in Sorong Regency is still very low and people's interest in becoming farmers is still very low, which causes the need for local food, especially vegetables. Low knowledge and skills of members of the Osok Women's Group (75% did not graduate from elementary school). The Osok women's group is dominated by indigenous Papuans who do not have sedentary jobs and have low education. There has been no effort developed in the Osok Women's Group and has not been maximized in the organizational arrangement of the group. The solution to the problems faced by Osok women is by conducting socialization and training in making compost planting media. The use of compost planting media was chosen because compost is proven to increase soil fertility naturally, is environmentally friendly, and has lower production costs compared to chemical fertilizers. This activity involves socialization and training to local communities regarding the manufacture and application of compost planting media in lettuce cultivation. Through composting techniques using local organic materials, such as plant residues, and organic waste. The stages of implementing the service are preparation, interviews, socialization of making compost planting media, training in making compost planting media, evaluation and reporting. The results of this activity show that this service activity shows several important results, both from agricultural and socio-economic aspects of the community. There is an increase in the knowledge and skills of the Osok Women's Group by 100%. 80% of organic household waste is converted into compost and there is an increase in household income of 5-10%. This activity has had a positive impact on the indigenous Papuan community in Sorong Regency, especially in optimizing the potential in a sustainable manner and increasing income. This program is expected to continue to grow and provide long-term benefits for the welfare of the local community.